CFD Analysis of Temperature Distribution of Different Piping Arrangements Used in Radiant Floor Heating System - Acharya, Ananta; Khanal, Shuvas; Humagain, Bishal; Kattel, Sangeet; Baral, Bivek (Kathmandu University Journal of Science, Engineering and Technology, 2021)
The rate of energy consumption on the household level for heating and cooling is increasing annually. Meeting future heating and cooling energy demand by alternative and promising technology like floor heating systems (FHS) should be the primary concern for engineers and designers. The floor heating system (FHS) maintains the desired indoor temperature with low-temperature fluid flowing inside the pipe than conventional heating systems. FHS has lower investment cost, lower energy consumption, better thermal comfort, and desired temperature up to human height. This paper aims to simulate and compare the temperature distribution for three different piping arrangements like double-wall serpentine, serpentine, and modulated spiral. The geometry was created in Solidworks. The system was modeled using sets of boundary conditions. The simulation results show that the spiral layout has a temperature distribution of 320 K at an outlet and has a temperature gradient of about 13°C between the inlet and outlet. This arrangement generates and heats the air uniformly in the room and provides better thermal comfort. Even serpentine has a small temperature gradient, and this system creates a periodic cycle of air movement in the room, which is the worst case in terms of thermal comfort. Doubled wall serpentine has a temperature gradient of 20°C, and this arrangement is the worst among the three layouts. The study concluded that spiral arrangement has a uniform temperature distribution among all the setup, heats the air uniformly, and provides better thermal comfort.